Biblical Account in the Pre-Shcool Education: Methodology and Practical Dimensions - Dimova, Iliana (Forum Theologicum Sardicense, 2025)
Biblical Account in the Pre-School Education: Methodology and Practical Dimensions. This article explores the current issues and prospects for the development of religious tourism in Bulgaria and its theological dimensions in the context of traditional pilgrimage.